Hemodynamic and cardiorespiratory responses to submaximal and maximal exercise in adults with Down syndrome - Oviedo, Guillermo R.; Carbó-Carreté, María; Guerra-Balic, Myriam; Tamulevicius, Nauris; Esquius, Laura; Guàrdia-Olmos, Joan; Javierre, Casimiro (Frontiers in Physiology, 2022)
Introduction: Down syndrome (DS) affects the cardiorespiratory and hemodynamic parameters. When exercising, sufficient blood flow is necessary for active muscles. Cardiac output (Q) must be proportional to the peripheral requirements. In case the stroke volume (SV) is lower, the heart rate (HR) will increase further in order to maintain an adequate blood flow in the active territories (HR compensatory response). People with DS have a lower HR response to maximal exercise. Nevertheless, the response of the hemodynamic and cardiorespiratory parameters during the submaximal phases of maximal exercise was not well studied. Objective: to evaluate cardiorespiratory and hemodynamic parameters (1) during submaximal and (2) maximal metabolic treadmill test in individuals with and without DS. Methods: fifteen adults with DS (age=27.33±4.98 y.o.; n=12 males/3 females) and 15 adults without disabilities, matched by age and sex, participated in this study. Peak and submaximal cardiorespiratory and hemodynamic parameters were measured during a treadmill test. Results: The DS group showed lower peak values for ventilation (VE), respiratory exchange ratio (RER), tidal volume (VT), ventilatory equivalent for O2 (VEqO2), end-tidal partial pressure for O2 (PETO2), O2 uptake (VO2) and CO2 production ( all p<.050), Q, SV, systolic and diastolic blood pressure (SBP, DBP), and HR (all p<.050). There were group-by-time interactions (all p<.050) for all ventilatory submaximal values. Significant group and time differences were observed for VE; RER; respiratory rate (RR); VEqO2; PETO2; VO2, and VT (all p<.050). There were also group-by-time interactions (all p<.050) and group and time differences for SBP, mean arterial blood pressure (MAP) and HR (all p<.010). Conclusion: During submaximal exercise, we verified a compensatory response of HR, and greater VE and VO2 in the individuals with DS. In addition, we were able to observe that the DS group had a reduced SBP and MAP response to submaximal exercise. On the other hand, we found that adults with DS have lower peak hemodynamic and cardiorespiratory values, and a lower cardiac reserve. Further research is warranted to investigate the effects of these results on the general health of adults with DS and the impact of long-term exercise programs on these parameters.